EVALUATION OF BACILLUS SPP. FOR PHOSPHATE SOLUBILIZATION AND PLANT GROWTH PROMOTION PRATIBHA - Pratibha Singh Chandel (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Plant growth-promoting rhizobacteria (PGPR) represent a group of free-living bacteria inhabiting the rhizospheric soil and improving plant growth. These PGPRs have a dynamic role in plant growth by serving as bio-fertilizers. Therefore, we focused the present research investigation on isolating and characterizing phosphate solubilization and PGPR-producing rhizobacteria. Twenty-two bacteria were isolated, from which three bacteria belong to Bacillus spp. and were shown PGPR activity. We examined phosphate solubilizing efficacy, ammonia secretion, hydrogen cyanide production, and IAA production to evaluate the PGPR efficacy of bacterial isolates. Bacillus sp. PGPR-1 exhibited significant phosphate solubilization (2.4 ±0.039 mm ±SD zone diameter) and IAA (16.2 ±0.12 µg/mL ±SD) production along with ammonia and hydrogen cyanide secretion. Bacillus sp. PGPR-1 has potentially been used as an additives to fortify bio-fertilizer for sustainable agricultural management.